Anatomical changes and evolutionary trends in the foliar epidermis of extant and fossil Euro-Mediterranean oaks (Fagaceae) - Uzunova, K.; Palamarev, E.; Ehrendorfer, F. (Plant systematics and Evolution, 1997)
The differentiation of foliar epidermis structures, cuticles, stomata, and indumen- turn of most of the extant Euro-Mediterranean taxa of Quercus have been studied by light and scanning electron microscopy, and compared with other genera and fossil material. Results allow the recognition of the subgg. Sclerophyllodrys, Cerris and Quercus, and of various sections and even individual species. The cyclocytic stomata type, regarded as plesiomorphic, is found in the geologically oldest representatives of the familiy (DryophylIum, resp. Eotrigonobalanus) and in the relatively old, evergreen to semi-evergreen species of Quercus subgg. Sclerophyllodrys and Cerris. These taxa also have relatively thick and smooth cuticles. Anomocytic stomata, thinner cuticles and the presence of crystalline wax flakes are regarded as apomorphic features and characterize the deciduous taxa ofsubg. Quercus. These changes are interpreted as ecological adaptations to the changing climates from the Tertiary to the present. An analysis of the various character combinations found in macrofossils and the often poor species separation i n Quercus suggest that hybridization has played a major role in the evolution of the Euro-Mediterranean oaks.
Keywords: epidermis characters; evolutionary trends; Fagaceae; fossil and extant taxa; Quercus